Technology in English Language Teaching and Learning: The Use of PowerPoint Games on Vocabulary Class at Universitas Islam Madura - Yuliawati, Fitrah; Bahrudin, Dinar Vincy Yunitaka; Rohaniyah, Jaftiyatur (Corolla International Conference, 2025)
The paper’s goal is to collect evidence of the many advantages of integrating technology into English language instruction, as well as any barriers and difficulties that may arise and how they are resolved. This study examines a number of experiences and advantages of using technology in Universitas Islam Madura’s vocabulary classes for English language instruction. Additionally, this paper outlines the obstacles that must be addressed in order to incorporate technology into language acquisition. Data is gathered by means of interviews. To understand more about the experiences, advantages, and difficulties of using technology for language acquisition, this study uses qualitative methods. There are 24 participants in this study. The findings indicate that incorporating technology into English language instruction through PowerPoint offers several advantages, including the ability for students to code, practice online tests or quizzes, increase their response times, improve their scores on English language assessments, learn a second language, engage in collaborative learning, promote self-directed learning, write, speak, listen, and read in English, use multiple computer programs, access the most recent information, translate, use multi-media presentations, and showcase innovative teaching techniques. The type of technology employed, the speed at which technology is developing, the number of classes taught, the size of the classes, the cost, time, age, and the workload of the lecturers, as well as the availability and proficiency of the technology, are some of the problems associated with technology integration.